EFEK KATALITIK Natrium-AlO2 PADA PROSES PENCAIRAN BATUBARA TANPA PELARUT HIDROGEN DONOR - Yuli Artanto; Yusnitati Yusnitati (Badan Pengkajian dan Penerapan Teknologi, 2006)
Indonesian brown coal, South Banko coal, was liquefied into oil in the presence ofcarbon monoxide and water using alkali base catalyst, NaAlO2. Liquefaction testwas carried out using microautoclave in the absence of donor solvent. Experimentwas conducted at 365oC and 400oC in order to examine the effect of temperatureon coal conversions.Kata kunci: south banko, brown coal, liquefaction, catalyst, donor solvent